Total asam, viskositas dan kesukaan yogurt buah pisang ambon (Musa paradisiaca) - Siti Rahmawati Zulaikhah; Restuti Fitria (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2020)
ABSTRACT Yogurt with the addition of probiotics is intended so that the benefits of lactic acid bacteria can survive until digestion. The starters used in this yogurt are Streptococcus thermophillus, Lactobacillus bulgaricus and Lactobacillus acidophilus. The addition of banana juice aims to utilize monosaccharides for LAB growth in producing metabolic products in the form of lactic acid so that it can affect the total acid, viscosity and consumer preferences. This study was conducted to determine the effect of the amount of natural Ambon banana fruit juice levels on total acid, viscosity and consumer preferences for the resulting yogurt. The benefits of this study are to determine the total acid content, viscosity and level of consumer preference for yogurt made with the addition of Ambon banana juice and to increase the potential of Ambon banana fruit. The research design in data collection used a randomized block design with 4 treatment levels of fruit juice (0% (T0), 2% (T1), 4% (T2), and 6% (T3) and was carried out in 3 blocks as replications. Observation of the total acid and viscosity if there is an effect of the treatment is carried out further tests with the Duncan multiple region test. The preference test was carried out using the Kruskal-Wallis non-parametric test. The results showed that the addition of Ambon banana juice levels (0%, 2%, 4% and 6%) did not have a significant effect on total acidity, viscosity and preference for yogurt. Yogurt with the addition of banana juice by 4% is the best based on the test results because it has good viscosity, low total acid content. Keywords: Banana yoghurt, total acid, viscosity, preference